Tren Penelitian Nyeri Bahu Post-Stroke: Tinjauan Bibliometrik Satu Dekade Terakhir - Muhammad Ardi; I Made Kariasa (Optimal Nursing Journal, 2024)
Introduction: Hemiplegic shoulder pain is one of the complications of stroke. This study aims to conduct a bibliometric analysis using VOSviewer regarding post-stroke shoulder pain published in 2013-2023. The literature search method was obtained from Scopus on February 19, 2024, using the keywords 'shoulder' AND 'pain' AND 'post-stroke'. Methods: The initial search found 202 publications, 182 publications using English. The type of publication was limited to reviews and articles, so there were 166 articles that met the criteria. VOSviewer was used to analyze the number of publications, countries, institutions, journals with the most publications, articles with the most citations, authors, and keywords. Results: China had the highest number of publications. The institution publishing the most research and citations was Department of Allied Health Professions, University of The West of England, Bristol, United Kingdom. Frontiers in neurology was the journal with the most publications (11 articles). Post stroke pain: Identification, assessment, and therapy was the most cited article (167 citations). Chen, H., and Jacinto, J., authored the most articles and contributed significantly to post-stroke shoulder pain research. Acupuncture, botulinum toxin, physical therapy, analgesia, electrical stimulation, and robotic were the topics discussed. Discussion: Bibliometric analysis showed an increase in post-stroke shoulder pain research in the last 10 years. Research and publications in different countries indicate global attention to post-stroke shoulder pain. Recent studies have highlighted the success of various therapies, including acupuncture, botulinum toxin and the use of robots in reducing pain and improving motor function. A multidisciplinary approach to therapy is required, taking into account patient characteristics and the severity of post-stroke pain.